1999
DOI: 10.1127/archiv-hydrobiol/145/1999/111
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and colonization of aquatic plant fragments in relation to the disturbance frequency of their habitats

Abstract: The regeneration (regrowth into viable plants) and colonization (establish ment in the sediment) abilities of vegetative fragments of 16 aquatic plant species occurring in habitats with different disturbance frequencies were compared through a laboratory experiment. The hypothesis was that plants occurring in habitats frequently disturbed by floods should have higher regeneration and colonization abilities than plants in rarely disturbed habitats. Four types of fragments were collected from the plants and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 0 publications
0
77
2
Order By: Relevance
“…stress was vulnerable to be damaged by hydraulic force, resulting in allofragments of the plant, rather than autofragments. The allofragments generally have much lower survival potential than the plant autofragments in both field and experiments (Kimbel, 1982;Barrat-Segretain, 1996;Madsen, 1997;Barrat-Segretain et al, 1999), mainly due to their lower carbohydrate storage, which plays an important role in vegetative propagule performance (Spencer & Ksander, 1996;Werger & Huber, 2006). Therefore, our results imply that submersed vegetations grown in eutrophic lakes are prone to produce much more allofragments, indicating much lower survival potential in habitats with frequent disturbances.…”
Section: Discussionmentioning
confidence: 71%
“…stress was vulnerable to be damaged by hydraulic force, resulting in allofragments of the plant, rather than autofragments. The allofragments generally have much lower survival potential than the plant autofragments in both field and experiments (Kimbel, 1982;Barrat-Segretain, 1996;Madsen, 1997;Barrat-Segretain et al, 1999), mainly due to their lower carbohydrate storage, which plays an important role in vegetative propagule performance (Spencer & Ksander, 1996;Werger & Huber, 2006). Therefore, our results imply that submersed vegetations grown in eutrophic lakes are prone to produce much more allofragments, indicating much lower survival potential in habitats with frequent disturbances.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, in four of the tested species here (M. spicatum, M. aquaticum, H. verticillata and C. demersum), regeneration started mostly by the production of new shoots, whereas in E. canadensis, E. nuttallii, E. najas and M. heterophyllum, predominantly a concurrent growth of new shoots and roots was documented right from the beginning of plant regeneration. This might cause higher colonization respectively uprooting rates in the field, but Barrat-Segretain et al (1998) and Barrat-Segretain and Bornette (2000) reported only a low percentage of colonization of regenerated fragments in E. canadensis. Fragments of other species were not found to root in the sediment (Barrat-Segretain and Bornette, 2000), but developed turions in autumn.…”
Section: Discussionmentioning
confidence: 99%
“…This might cause higher colonization respectively uprooting rates in the field, but Barrat-Segretain et al (1998) and Barrat-Segretain and Bornette (2000) reported only a low percentage of colonization of regenerated fragments in E. canadensis. Fragments of other species were not found to root in the sediment (Barrat-Segretain and Bornette, 2000), but developed turions in autumn.…”
Section: Discussionmentioning
confidence: 99%
“…appear to outcompete other aquatic macrophytes after mechanical clearing of water bodies (HowardWilliams et al 1996;Abernethy et al 1996). Second, many aquatic macrophytes proliferate by cut-off fragments (Barrat-Segretain & Bornette 2000;Mielecki & Pieczynska 2005), making it critical that the method of mechanical cutting not itself be counterproductive.…”
Section: Titelmentioning
confidence: 99%